Pyridine-substituted BODIPY as fluorescent probe for Hg2+ - Wagner, Sally; Brödner, Kerstin; Bunz, Uwe H. F. (European journal of organic chemistry, 2012)
Dialkynylated BODIPYs bearing pyridine or dibutylaniline substituents have been synthesized, and their photophyisical properties in the presence of different metal ions have been studied. 4-Pyridyl substitution gives a highly selective fluorescence probe for HgII ions.